2011
DOI: 10.1016/j.clim.2010.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylserine reduces immune response against human recombinant Factor VIII in Hemophilia A mice by regulation of dendritic cell function

Abstract: A major clinical complication in the treatment of Hemophilia A using exogenously administered recombinant Factor VIII (FVIII) is the development of neutralizing antibodies. It has been shown previously that FVIII complexed with phosphatidylserine (PS) reduces the development of total and neutralizing antibody titers in hemophilic mice. The effect of complexation of FVIII with PS upon dendritic cell (DC) uptake, maturation and processing, T-cell proliferation and cytokine secretion profiles was investigated. Fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 40 publications
2
32
0
Order By: Relevance
“…In addition to the study carried out here, more mechanistic studies are needed to confirm that PS- mediated tolerance induction is functioning in an antigen specific manner, which is independent of the antigen that is co-administered, to induce tolerance. To accomplish this, future studies will be carried out for rhGAA as they were for FVII to further demonstrate the roles of TGF-β, regulatory T cells, and memory B cells in vivo, and to compare the results to what was previously observed for FVIII 36 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the study carried out here, more mechanistic studies are needed to confirm that PS- mediated tolerance induction is functioning in an antigen specific manner, which is independent of the antigen that is co-administered, to induce tolerance. To accomplish this, future studies will be carried out for rhGAA as they were for FVII to further demonstrate the roles of TGF-β, regulatory T cells, and memory B cells in vivo, and to compare the results to what was previously observed for FVIII 36 .…”
Section: Discussionmentioning
confidence: 99%
“…The studies aimed at understanding the mechanism of this reduction showed that FVIII-PS down-regulated the expression of CD40 upon exposure to bone marrow-derived dendritic cells (DC) (4). Further, T-cell activation studies wherein the incubation of FVIII-PS exposed DC with FVIII-primed splenic CD4…”
mentioning
confidence: 99%
“…Phosphatidylserine exposure on the outer cell membrane is a hallmark of apoptosis and is recognized by receptors on phagocytes in a manner that hinders immunogenic responses to the cell-derived components. When chemically conjugated to recombinant Factor VIII and administered to hemophilic mice, the incorporated phosphatidylserine effectively reduced DC activation, drove T cell expression of IL-10 and TGF-b, and induced FoxP3 + regulatory T cells (Tregs) [24]. By deceiving APCs into recognizing the therapeutically administered Factor VIII as a product of an apoptotic cell, Gaitonde and colleagues were able to induce tolerance to the therapeutic protein in mice and enabled follow-on treatment with wild-type Factor VIII without the generation of antiFactor VIII antibodies [25].…”
Section: Antigen Targeting To Dendritic Cellsmentioning
confidence: 99%